Smart(en)ing the Arctic city? The cases of Kiruna and Malmberget in Sweden - Rizzo, Agatino; Sjöholm, Jennie; Luciani, Andrea (European Planning Studies, 2024)
In this article, we problematize the implementation of smart urban experiments in the resource-rich, Arctic periphery. Our case study is the so-called Norrbotten Technological Megasystem in Sweden, with a specific focus on the mining towns of Malmberget/Gällivare and Kiruna. Kiruna in particular is a well know case study as its urban centre is being relocated due to subsidence caused by underground mining. The new town centre is being developed as a testbed for smart urbanism. We argue that if we look at the nexus between resource extraction and urbanization in Kiruna and Malmberget, we find smart city thinking more aligned to the bottom line of the resource extraction industry rather than being an innovative project to make economic development compatible with broader climate and societal challenges. Methodologically, we use historic analysis and assemblage thinking to look at the territorialization and de-territorialization of resource-extraction in Norrbotten over the last 100 years. Validerad;2024;Nivå 2;2024-03-22 (hanlid); Full text license: CC BY 4.0 Funder: Kiruna Council Eco-district